Developing fuzzy logic strength of evidence index and application in Bayesian networks for system risk management. (15th April 2022) - Lu, Liangliang; Goerlandt, Floris; Banda, Osiris A. Valdez; Kujala, Pentti
Highlights: A fuzzy SoE (strength of evidence) index is developed based on fuzzy logic theory. The ambiguity issue of SoE raised in the literature in risk analysis is tackled. Full digitalization of all elements in risk R C, P, S o E BK ) is enabled. The integration of fuzzy SoE index to BNs (Bayesian networks) is demonstrated. Their integrated features showcase an improved system risk management approach. Abstract: Digitalization is becoming a trend in our modern society and systems. Meanwhile, risk analysis and management has rooted and been applied in various fields. Therefore, there is an increasing need to integrate risk analysis and management into the coming digital society. Risk has been represented digitally by the product of probability and consequence i.e. R = P × C traditionally. However, it has been increasingly discussed to include strength of evidence (SoE) in addition to the traditional consequence (C) and probability (P). Although much advance has been achieved along this direction, there still remains challenges, e.g. ambiguity in rating SoE and visual expression of risk diagrams. This paper focuses on addressing these issues and meanwhile aims to make the risk expression fully digital so that it is more efficient and flexible to be included in a system analysis and visualization. This is achieved firstly by reviewing state-of-the-art discussions on SoE assessment in risk management and identifying the remaining challenges. Then, the paper proposes an approach to address the challenges by forming a fuzzy logic SoE index based on fuzzy logic theory, which enables a transfer from linguistic variable to a digital one with the ambiguity avoided. After the SoE index is formed, it is applied into BNs as the node size index to demonstrate its practical application. Meanwhile, with the BNs forming the infrastructure to calculate and present consequences and probabilities, it showcases a new system risk management approach. All the variables in the system can be expressed in a risk diagram. This further enables an improved risk visualization, risk management and risk communication for system analysis, towards risk digitalization.